2017
DOI: 10.3390/app7040417
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature Field on Low Amplitude Oscillatory Flow within a Parallel-Plate Heat Exchanger in a Standing Wave Thermoacoustic System

Abstract: Thermoacoustic technologies rely on a direct power conversion between acoustic and thermal energies using well known thermoacoustic effects. The presence of the acoustic field leads to oscillatory heat transfer and fluid flow processes within the components of thermoacoustic devices, notably heat exchangers. This paper outlines a two-dimensional ANSYS FLUENT CFD (computational fluid dynamics) model of flow across a pair of hot and cold heat exchangers that aims to explain the physics of phenomena observed in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Hence, the transition model seems to be a better model for predicting the flow at this drive ratio. The difference in amplitude of velocity between experimental and numerical results at ϕ5 and ϕ15 may be due to the moderation constant [21,23,26,27] not being varied in this study.…”
Section: Turbulent Flow Modelsmentioning
confidence: 86%
See 2 more Smart Citations
“…Hence, the transition model seems to be a better model for predicting the flow at this drive ratio. The difference in amplitude of velocity between experimental and numerical results at ϕ5 and ϕ15 may be due to the moderation constant [21,23,26,27] not being varied in this study.…”
Section: Turbulent Flow Modelsmentioning
confidence: 86%
“…It is at 0.17 from the pressure antinode. The electrical heating elements in HHX and cooling water flow in CHX aim to provide flat temperature profiles over the fins: 200 °C and 30 °C, respectively; but in practice, the heat leaks produce a slightly distorted temperature distribution as reported in [17] and [21]. Particle image velocimetry (PIV) and planar laser-induced fluorescence (PLIF) techniques provide the oscillatory velocity and temperature field information around the heat exchangers.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the fact that the flow is oscillatory and the existing knowledge for steady flow arrangements is of little practical value [11][12][13]. As a consequence, standard heat transfer correlations for steady flows cannot be directly applied to thermoacoustic HXs, for which reliable and unambiguous design criteria are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Saat and Jaworski [12] proposed a friction factor correlation applicable to a larger mesh range for a regenerator in a travelling-wave thermoacoustic system, based on experimental and CFD studies. They also studied the effects of temperature field, gravity and device orientation on the oscillatory flow [13]. Hsu and Biwa [14] carried out an experimental study on the heat flow in different mesh screen regenerators and compared the experimental result with four empirical equations, and concluded that all four empirical equations reproduce the measured heat flow rates to a similar degree.…”
Section: Introductionmentioning
confidence: 99%